Anti-tumor Effect of Oleic Acid in Hepatocellular Carcinoma Cell Lines via Autophagy Reduction - Giulitti, Federico; Petrungaro, Simonetta; Mandatori, Sara; Tomaipitinca, Luana; de Franchis, Valerio; D'Amore, Antonella; Filippini, Antonio; Gaudio, Eugenio; Ziparo, Elio; Giampietri, Claudia (Frontiers in Cell and Developmental Biology, 2021)
Oleic acid (OA) is a component of the olive oil. Beneficial health effects of olive oil are well-known, such as protection against liver steatosis and against some cancer types. In the present study, we focused on OA effects in hepatocellular carcinoma (HCC), investigating responses to OA treatment (50-300 μM) in HCC cell lines (Hep3B and Huh7.5) and in a healthy liver-derived human cell line (THLE-2). Upon OA administration higher lipid accumulation, perilipin-2 increase, and autophagy reduction were observed in HCC cells as compared to healthy cells. OA in the presence of 10% FBS significantly reduced viability of HCC cell lines at 300µM through Alamar Blue staining evaluation, and reduced cyclin D1 expression in a dose-dependent manner while it was ineffective on healthy hepatocytes. Furthermore, OA increased cell death by about 30%, inducing apoptosis and necrosis in HCC cells but not in healthy hepatocytes at 300µM dosage. Moreover, OA induced senescence in Hep3B, reduced P-ERK in both HCC cell lines and significantly inhibited the antiapoptotic proteins c-FLIP and Bcl-2 in HCC cells but not in healthy hepatocytes. All these results led us to conclude that different cell death processes occur in these two HCC cell lines upon OA treatment. Furthermore, 300 µM OA significantly reduced the migration and invasion of both HCC cell lines, while it has no effects on healthy cells. Finally, we investigated autophagy role in OA-dependent effects by using the autophagy inducer torin-1. Combined OA/torin-1 treatment reduced lipid accumulation and cell death as compared to single OA treatment. We therefore concluded that OA effects in HCC cells lines are, at least, in part dependent on OA-induced autophagy reduction. In conclusion, we report for the first time an autophagy dependent relevant anti-cancer effect of OA in human hepatocellular carcinoma cell lines.